PERAN KEPALA SEKOLAH DALAM MANAJEMEN PROGRAM EMPOWERING DI SMA ISLAM KEPANJEN - Vindi Septianti; Ibrahim Bafadal; Imron Arifin; Vindi Septianti; Ibrahim Bafadal (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: The purpose of this study is to describe; (1) the role of the principal in preparing the empowering program plan in Kepanjen Islamic High School; (2) the role of the principal in the implementation of the empowering program in Kepanjen Islamic High School; (3) the role of the principal in evaluating the empowering program in Kepanjen Islamic High School; (4) supporting factors and obstacles to the role of the principal in the management of empowering programs in Kepanjen Islamic High School. This study uses a qualitative approach to the type of case study research. Kepanjen Islamic High School research location. Data collection techniques used were observation, interviews and documentation. The key informant in this study was the Principal of Kepanjen Islamic High School. The results of the study, namely: 1) the role of the principal in the preparation of the empowering program plan at Kepanjen Islamic High School includes the timing of the preparation of the empowering program plan, the formation of the empowering program group, the parties involved in the preparation of the empowering program, the strategy of preparing the empowering program and the role of the principal in the preparation planned empowering program at Kepanjen Islamic High School; 2) the role of the principal in the implementation of the empowering program which includes the background of the implementation of the empowering program, the implementation schedule of the empowering program, the empowering program activities, the organizational structure in the empowering program, and the role of the principal in the management of the empowering program in Kepanjen Islamic High School; 3) the role of the principal in evaluating the empowering program in Kepanjen Islamic High School which includes the empowering program evaluation system, the parties involved in evaluating the empowering program, how to measure the success of the empowering program, the principal's supervision of the empowering program manager and instructor, the role of the principal in the evaluation of the empowering program, and follow up on the evaluation of the empowering program; 4) supporting factors and obstacles to the role of the principal in the management of the empowering program in Kepanjen Islamic High School which include supporting factors, inhibiting factors, and solutions to overcome the obstacles of the empowering program in Kepanjen Islamic High School